Multi-Objective Optimization of the Electro-Discharge Diamond Surface Grinding Process - Sunder, Shyam; Yadava, Vinod (Asian Review of Mechanical Engineering, 2012)
Grinding of Metal matrix composites (MMCs) which are making inroads in various engineering applications have proved to be extremely difficult to machine due to presence of hard ceramic reinforcement. Electro-discharge machining (EDM) of MMCs containing electrically non conducting phases possess few problems in terms of hampering the process stability and impeding the material removal process. Use of combination of grinding and EDM has potential to overcome these problems. This article presents the optimization design of an electro-discharge diamond surface grinding (EDDSG) process performed on aluminum-metal matrix composite (Al-MMC). The major performance characteristics selected to evaluate the process are material removal rate (MRR) and average surface roughness (Ra). The input machining parameters used in the present study were current, pulse on-time, wheel speed, and duty factor. Experiments were carried out on newly self developed surface grinding setup for electro-discharge diamond grinding (EDDG) process for Al-10wt.%SiCp composites. The experimentations are planned as per L9 orthogonal array. Grey relational analysis (GRA) is used for optimizing the machining parameters. Principal component analysis (PCA) is coupled with GRA to evaluate the weighting values corresponding to various performance characteristics that their relative importance can be properly described. The most significant factor has been found as pulse on-time effecting the robustness of electrodischarge diamond surface grinding (EDDSG) process.